Observed bottom warming in the East Siberian Sea driven by the intensified vertical mixing - Xiaoyu Wang; Longjiang Mu; Xianyao Chen (Ocean Science, 2025)
The East Siberian Sea (ESS) features the broadest continental shelf on Earth and contains nearly 80 % of the world's subsea permafrost. A persistently cold bottom layer, with temperatures at freezing point, inhibits the downward transport of heat, thus preventing the thawing of permafrost and subsequent methane release from sediments. However, in early September 2016, we observed an unprecedented warming of over 3 °C at the bottom of the water column, approximately 46 m deep in the ESS, following a relatively moderate Arctic cyclone. We attribute this notable bottom warming to enhanced wave-induced vertical mixing, which facilitates the well-mixed Arctic marginal seas and allows surface heat to reach the bottom layer. As sea ice continues to retreat on the Arctic continental shelf, wind-driven waves have longer fetch to grow. Consequently, even moderate cyclones can trigger substantial vertical mixing, a phenomenon not previously documented. Given the accelerated warming of the Arctic and the rapid decline of sea ice, we anticipate that more open water will foster the growth of larger wind-driven waves and intensified vertical mixing, leading to greater heat influx to the bottom layers of Arctic shelves in the future.

Influence of grounding giant iceberg D15 on sea ice and polynyas in a sea ice-ice shelf-ocean numerical model of the Prydz Bay, Antarctica - Quanyi Zhou; Jiuxin Shi; Chuning Wang; Longjiang Mu; Zhigang Yao; Zhaoru Zhang; Yuxin Han; Yongming Sun (Acta Oceanologica Sinica, 2025)

The detection of Arctic sea ice linear kinematic features using LadderNet - Junting Chen; Longjiang Mu; Xiaoyi Jia; Xianyao Chen (Ocean Modelling, 2024)

Evaluation of Arctic Sea-ice Cover and Thickness Simulated by MITgcm - Fei Zheng; Yue Sun; Qinghua Yang; Longjiang Mu (Advances in Atmospheric Sciences, 2021)

Turbulent mixing above the Atlantic Water around the Chukchi Borderland in 2014 - Wenli Zhong; Guijun Guo; Jinping Zhao; Tao Li; Xiaoyu Wang; Longjiang Mu (Acta Oceanologica Sinica, 2018)

Regime shift of the dominant factor for halocline depth in the Canada Basin during 1990–2008 - Longjiang Mu; Jinping Zhao; Wenli Zhong (Acta Oceanologica Sinica, 2017)

Regional characteristics of sea ice thickness in Canadian shelf and Arctic Archipelago measured by Ground Penetrating Radar - Tao Li; Jinping Zhao; Yutian Jiao; Jiaqiang Hou; Longjiang Mu (Acta Oceanologica Sinica, 2015)